2022
DOI: 10.1186/s12872-022-02879-0
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcification in patients with advanced chronic kidney disease

Abstract: Introduction Cardiovascular disease (CVD) is associated with higher morbidity and mortality rates in patients with chronic kidney disease (CKD). Studies have shown that vascular calcification is a major predictor of CVD. Vascular calcification in the CKD population is associated with various risk factors, and changes in bone and mineral metabolism have been linked to an increased risk of atherosclerosis. Therefore, we aimed to investigate the correlation between vascular calcification and bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Studies have shown that iPTH can enhance cartilage matrix expression and intracellular calcium levels, thereby facilitating the development of VC. VC can be caused by both high and low iPTH levels 33 . As previously stated, vascular calcification is an active and controllable process, and metabolic calcium and phosphorus deposition can cause calcification changes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that iPTH can enhance cartilage matrix expression and intracellular calcium levels, thereby facilitating the development of VC. VC can be caused by both high and low iPTH levels 33 . As previously stated, vascular calcification is an active and controllable process, and metabolic calcium and phosphorus deposition can cause calcification changes.…”
Section: Discussionmentioning
confidence: 99%
“…Because all included patients in the current study had CKD, a well-known risk factor for cardiovascular disease [20], our findings suggest that gout may impose added risk on CKD patients. The possibly synergistic impact of gout and CKD on CAC may contribute as CAC scores are positively correlated with rates of cardiovascular hospitalization and all-cause death [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that iPTH can enhance cartilage matrix expression and intracellular calcium levels, thereby facilitating the development of VC. VC can be caused by both high and low iPTH levels 33 . As previously stated, vascular calci cation is an active and controllable process, and metabolic calcium and phosphorus deposition can cause calci cation changes.…”
Section: Discussionmentioning
confidence: 99%